Answer:
=40b+24
Step-by-step explanation:
Answer:
not enough info
Step-by-step explanation:
f times x equals -3 there could be many answers like f is 1 x is -3 or f is -3 x is 1 and more
Answer:
-6.5
Step-by-step explanation:
-2(p - 1) = 15
-2p + 2 = 15
-2p = 13
p = -6.5
Answer:
y= -4
Step-by-step explanation:
x+y=42. We know that x plus y equals 42.
x=2y . We also know that x equals twice y.
2y+y=42. Since we know that x=2y, we're going to replace x with 2y from the original equation, simplified would be 3y=42.
y=14. 3y=42 simplified is y=14, this is because we divided both sides by 3 (since 3 and 42 are both divisible by 3) (btw divisible by 3 simply means that it can be divided by 3)
x+14=42. Now that we know what y equals, let's replace y with 14 from the original equation.
x=28. Now that we know that x=28 and y=14, we know that y is always x/2.
When x=-8, we divide it by 2 and get, -4.
Not absolutely positive as this was all mental math, but hope this helps! :)